Umbral or the autobiographical ambiguity - Alberca, Manuel (Círculo de Lingüística Aplicada a la Comunicación, 2012)
In this article the most peculiar features of the Spanish autofiction are shown, as well as the contradictory reasons to explain its development, the relation with autobiography and the place where it stands between autobiography and the novel. To analize and exemplify this set of problems, in the second part of the article I refer to Francisco Umbral’s work, whose autofictions play hide and seek in the endless world of the novel.